Use of cultural plants in desert cities in creating the landscape of recreation zones in Uzbekistan - Muhayyo Sultanova (Research Parks Publishing LLC, 2020)
In Uzbekistan, at the present time, the goal is to analyze and evaluate the existing capacities of the geo-complexes, to identify the urgent problems and to develop them on scientific and practical basis, it is important to develop ways to solve them. Therefore, geographically, it is one of the important issues for our country to consider the desert areas. Landscape of the mountainous areas of the Republic is the main center of the city. In particular, it is important to create reclamation zones, which contribute significantly to landscaping, both locally and locally, due to the social life of the population. Sustainable environmental sustainability is a major issue in the creation of a recreation area in the steppe. Recreation zone should be kept in desert conditions and cleaned by its dusty air. In one of the desert regions, cultivation of different types of trees in the areas of recreation can be beneficial not only for the sake of recreation, but also to keep the air clean.